Reflective Learning as a Response to Contemporary Educational Challenges - Anna Perkowska-Klejman (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Introduction: Learning and teaching - especially the formal one - usually followed certain patterns that were considered appropriate for the times. Aim: This paper is devoted to reflective learning in the context of contemporary educational challenges. Evidence-based Facts: Reflective learning is based on conscious reflection about one's knowledge, beliefs, and cognitive processes. Reflectiveness relates to both the person and the learning contexts. It also involves learning about other positions and points of view. Reflective learning considerations are based on constructivism and critical theories. Reflectiveness in education allows for a student to be treated as an active subject of education, who creates and not simply reproduces existing knowledge. Significant consideration is given to the learning context. Reflective learning is also aimed at finding the most efficient solutions for resolving complex problems. Finally, the paper presents challenges in the context of reflectivity in education that are related to the demystification of power mechanisms and the opportunities for emancipation. Summary: The article presents reflexivity as an important attribute of  present-day  education. Reflexivity in education recognize the relationship between the subjective perspective of the subject and the social context , that creates the living space of learners.